Cellular and molecular mechanisms of asthma and COPD - Barnes, Peter J. (Clinical science (1979), 2017)
Asthma and chronic obstructive pulmonary disease (COPD) both cause airway obstruction and are associated with chronic inflammation of the airways. However, the nature and sites of the inflammation differ between these diseases, resulting in different pathology, clinical manifestations and response to therapy. In this review, the inflammatory and cellular mechanisms of asthma and COPD are compared and the differences in inflammatory cells and profile of inflammatory mediators are highlighted. These differences account for the differences in clinical manifestations of asthma and COPD and their response to therapy. Although asthma and COPD are usually distinct, there are some patients who show an overlap of features, which may be explained by the coincidence of two common diseases or distinct phenotypes of each disease. It is important to better understand the underlying cellular and molecular mechanisms of asthma and COPD in order to develop new treatments in areas of unmet need, such as severe asthma, curative therapy for asthma and effective anti-inflammatory treatments for COPD.